INFLUENCE OF FETOPLACENTAL INSUFFICIENCY ON THE FORMATION OF PERINATAL PATHOLOGY IN PRETERM NEONATES - N. P. Molokanova; L. K. Gavrikov (Вопросы современной педиатрии)
Aim: to identify features of early neonatal period in preterm infants of women with fetoplacental insufficiency (FPI). Patients and methods: we conducted a retrospective study of early neonatal period in 76 preterm infants with gestational age from 28 to 36 weeks. Of these, 31 were born by women with FPI (study group) and 45 neonates from mothers without complications during pregnancy (control group). We analyzed course of pregnancy and delivery in both groups. Infant’s conditions were assessed using Apgar and Silverman Score. Neurological status, severity of respiratory and cardio-vascular failure were take into account in the first 7 days of life. Results: women with FPI had significantly higher levels of total extragenital pathology, hypertension was found only in mothers of the main group. The extent of Doppler abnormalities in most cases was light, while the most severe 3d grade was detected only in 4 women (12,9%), which had caused the birth of infants in severe asphyxia. Pathology of respiratory and central nervous system was dominated in preterm infants of both groups. Conclusions: the number of infants with serious conditions born by mothers with FPI is significantly higher than that determined by the deterioration of the utero-placental blood flow. Preterm neonates in women with FPI form a risk group of perinatal asphyxia.